Rare genetic variants involved in multisystem inflammatory syndrome in children: a multicenter Brazilian cohort study - Reis, Bárbara Carvalho Santos Dos; Soares Faccion, Roberta; de Carvalho, Flavia Amendola Anisio; Moore, Daniella Campelo Batalha Cox; Zuma, Maria Celia Chaves; Plaça, Desirée Rodrigues; Salerno Filgueiras, Igor; Leandro Mathias Fonseca, Dennyson; Cabral-Marques, Otavio; Bonomo, Adriana Cesar; Savino, Wilson; Freitas, Flávia Cristina de Paula; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Despite the existing data on the Multisystem Inflammatory Syndrome in Children (MIS-C), the factors that determine these patients evolution remain elusive. Answers may lie, at least in part, in genetics. It is currently under investigation that MIS-C patients may have an underlying innate error of immunity (IEI), whether of monogenic, digenic, or even oligogenic origin. To further investigate this hypothesis, 30 patients with MIS-C were submitted to whole exome sequencing. Analyses of genes associated with MIS-C, MIS-A, severe covid-19, and Kawasaki disease identified twenty-nine patients with rare potentially damaging variants (50 variants were identified in 38 different genes), including those previously described in IFNA21 and IFIH1 genes, new variants in genes previously described in MIS-C patients (KMT2D, CFB, and PRF1), and variants in genes newly associated to MIS-C such as APOL1, TNFRSF13B, and G6PD. In addition, gene ontology enrichment pointed to the involvement of thirteen major pathways, including complement system, hematopoiesis, immune system development, and type II interferon signaling, that were not yet reported in MIS-C. These data strongly indicate that different gene families may favor MIS-C development. Larger cohort studies with healthy controls and other omics approaches, such as proteomics and RNAseq, will be precious to better understanding the disease dynamics.